Fibro-Lipo-Lymph-Aspiration With a Lymph Vessel Sparing Procedure to Treat Advanced Lymphedema After Multiple Lymphatic-Venous Anastomoses: The Complete Treatment Protocol. Issue 2 (February 2017) - Campisi, Corrado Cesare; Ryan, Melissa; Boccardo, Francesco; Campisi, Corradino
Abstract : Background: In lymphedema, excess adipose tissue occurs with progression of the disease because of chronic lymph stasis, impeding lymphatic flow. Recently, liposuction has been used as a less-invasive procedure to remove this excess tissue. Given the existing poor lymph drainage in patients with lymphatic diseases, extra caution should be taken to avoid damaging lymphatic vessels during liposuction. We developed a new technique (Fibro-Lipo-Lymph-Aspiration with a Lymph Vessel Sparing Procedure [FLLA-LVSP]) to improve chronic swelling in patients with advanced lymphedema. The FLLA-LSVP highlights the superficial lymphatic pathways in the treated limb. This visibility allows surgeons to avoid these pathways, while removing the maximum amount of excess tissue. Method: One hundred forty-six patients with primary or secondary lymphedema that had already been treated by lymphatic microsurgery, in Genoa, Italy, were included in this retrospective study. All patients had residual fibrotic/adipose tissue, resistant to conservative treatments. Indocyanine green fluorescent dye and Blue Patent Violet dye were injected laterally/medially to the main superficial veins at the wrist/ankle of the limb to be treated. Using a photodynamic camera, the superficial lymphatic network was made visible and sketched onto the skin in indelible ink. After the microlymphography, the excess adipose tissue was carefully aspirated. Preoperative and postoperative excess limb volume was calculated using circumferential measurements and the formula of a frustum. Results: For the upper limb, 0.80 L, on average, and 2.42 L for the lower limb were removed with the FLLA-LVSP. For the upper limb, there was an average presurgery excess volume of 20.19%, which reduced to 2.68% after the FLLA-LVSP (Z score = −6.90, P < 0.001). Similarly, for the lower limb, there was an average presurgery excess limb volume of 21.24% and a reduction to 2.64% postoperatively (Z score = −3.57, P < 0.01). Immediate postoperative microlymphography and Blue Patent Violet test confirmed no lymphatic complications. No episodes of postoperative infection occurred. Conclusions: The FLLA-LVSP is efficient. An entire leg can be completed within 90 minutes. Recovery time is short, and cosmetic results are immediate. More importantly, the removal of excess tissue is completed without further damage to lymphatic vessels. When used after microsurgery, FLLA-LVSP offers the possibility of removing almost all obstacles to lymphatic flow.